(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Learning is a process that involves active interaction between students, educators, and various learning resources in an environment that supports learning. In the context of badminton learning, low student learning outcomes are thought to be caused by the lack of learning motivation possessed by students. This can be seen from the lack of seriousness of students in participating in badminton learning activities, which reflects a low interest in the material. This study aims to determine how high the level of students’ skills is in carrying out backhand and forehand service in badminton through the application of a playing approach. The type of research used is Classroom Action Research (CAR), with a qualitative descriptive approach, which is implemented at the Junior High School (SMP) level. At the pre-cycle stage, students who could meet the technical test completion criteria, backhand and long forehand service, were only 13 people or around 40%. After the learning action through the play method was carried out in cycle I, the number of students who succeeded increased to 19 students or 59%. Then in cycle II, there was a more significant increase, namely 25 students or around 78% who were able to do the technique service backhand and long forehand service following the indicators set out in the assessment instrument.